THERMOREGULATION IN CHILDREN: EXERCISE, HEAT STRESS & FLUID BALANCE - Shawnda A. Morrison (Annales Kinesiologiae, 2014)
This review focuses on the specific physiological strategies of thermoregulation in children, a brief literary update relating exercise to heat stress in girls and boys as well as a discussion on fluid balance strategies for children who are performing exercise in the heat. Both sport performance and thermoregulation can be affected by the body’s water and electrolyte content. The recommendations for pre-pubertal fluid intake have been generalized from adult literature, including a limited concession for the physiological differences between adults and children. Considering these body fluid shifts, carbohydrate-electrolyte drinks are thought to be an essential tool in combating dehydration as a result of active hyperthermia (i.e. exercise), thus we examine current hydration practices in exercising children. Finally, this review summarizes research which examines the relationship between cognition and hypohydration on young athletes’ performance.